Exploring EFL Students’ Perception on Student Engagement through the Use of Kahoot! on Learning Activities - Radhautul Jannah, Aulia (LPPM Universitas Pancasakti Tegal, 2024)
The integration of technology in English as a Foreign Language (EFL) classrooms has increasingly influenced student engagement and learning experiences. This study aimed to explore EFL students’ perceptions of student engagement through the use of Kahoot! in English language learning activities. Employing a qualitative case study design, data were collected through questionnaires and semi-structured interviews involving EFL students who had experience using Kahoot! in English classes. The qualitative data were analyzed thematically, while descriptive statistics were used to support the findings. The results revealed that most students perceived Kahoot! as an engaging and motivating learning tool that enhanced classroom interaction and reduced boredom during English learning activities. Students reported increased enthusiasm, active participation, and improved understanding of learning materials, particularly in vocabulary and grammar. The competitive and interactive features of Kahoot! were found to foster behavioral, cognitive, and social engagement. However, several challenges were also identified, including technical issues, internet connectivity constraints, and difficulties related to the fast-paced nature of the game for some learners. Overall, the findings suggest that Kahoot! plays a positive role in promoting student engagement and creating an interactive learning environment in EFL classrooms. The study highlights the importance of thoughtful instructional design and technical readiness to maximize the benefits of game-based learning tools in English language education.